Influence of Heat Treatment on the Corrosion of Carbon Steel in Environment Containing Carbon Dioxide and Acetic Acid - Adham Adnan, M. (Institute of Physics Publishing, 2018)
Experimental investigations were carried out to study the influence of heat treatment on the corrosion behaviour of API 5L X65 pipeline steel in the presence of acetic acid HAc and carbon dioxide CO2 environment. CO2 corrosion has been recognized as one of corrosion threats resulting in a loss of pipeline integrity. In this work, the specimens taken from the X65 steel pipe were subjected to respective heat treatment which was annealing, normalizing and quenching. As-received specimens were included as control. CO2 corrosion experiments using three-electrode glass cell system were performed with and without acetic acid. Corrosion rates were measured by means of weight loss and Linear Polarization Resistance (LPR) electrochemical methods. Results showed that heat treatments were found to affect the corrosion rates. Annealed specimen showed the lowest corrosion rate while quenched specimen appeared to corrode more compared to other specimens. The presence of acetic acid in aqueous CO2 environment generally aggravated the corrosion rate for all heat-treated specimens. Â© Published under licence by IOP Publishing Ltd.